2004
DOI: 10.3354/meps267209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amino acids on larval metamorphosis of the polychaete Hydroides elegans

Abstract: The inductive compounds that are cues for for the settlement and metamorphosis of polychaete Hydroides elegans larvae, isolated from adult homogenate of the same species and leachate of the bryozoan Bugula neritina, are known to be a mixture of amino acids. Here we investigated the toxicity of 20 amino acids on competent larvae. Nine amino acids were found to be toxic at certain concentrations. Subsequently, 12 out of 20 amino acids were assayed for their effect on larval metamorphosis of H. elegans. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Therefore, as long as there are bacteria in testing vessels, addition of chemical extracts or compounds into the vessels will selectively change the bacterial community structures in the testing vessels as shown by Jin & Qian (2004) and by this study.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Therefore, as long as there are bacteria in testing vessels, addition of chemical extracts or compounds into the vessels will selectively change the bacterial community structures in the testing vessels as shown by Jin & Qian (2004) and by this study.…”
Section: Discussionmentioning
confidence: 67%
“…Previous work (Jin & Qian 2004) suggested that Asp, Glu, Ala, Asn, Leu, Thr and Val could induce larval settlement of Hydroides elegans directly and Ile could not. In the present study, these amino acids showed different effects on bacterial communities of biofilms and the competent larvae of H. elegans responded variously to the modified biofilms.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Larvae of Hydroides elegans have been observed to prefer older biofilms, which commonly have higher bacterial densities (Jin & Qian 2004). The present study confirms those findings.…”
Section: Natural Biofilms Bacterial Densities and Community Profilesmentioning
confidence: 99%